2015
DOI: 10.3906/kim-1501-144
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of novel fused triazolo[4,3-$a$] pyrimidinones

Abstract: The reaction of thione 3 or its 2-methylthio derivative 4 with hydrazonoyl halides 5a-l, in the presence of triethylamine, yielded the corresponding triazolo[4,3-a ]pyrimidin-5(1 H) -ones 8a-l. The structure of compounds 8a-l was further confirmed by the reaction of 3 with the appropriate active chloromethylenes 11a-c followed by coupling of the products with benzenediazonium chloride to afford the azo-coupling products 6b, f, and j, which were converted in situ to 8b, f, and j. 2-Hydrazinyl-pyrido[3',2':4,5]t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 17 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…[42] S C H E M E 2 Synthesis of [1,2,4] Synthesis of a related fused [1,2,4]triazole nucleus was achieved via the reaction of 26 with the appropriate hydrazonyl chlorides 10. [24] Thus, compound 26 reacted with hydrazonyl chloride 10a in dioxane in the presence of an equivalent amount of triethylamine. The reaction mixture was heated at reflux till no methanethiol gases were evolved.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…[42] S C H E M E 2 Synthesis of [1,2,4] Synthesis of a related fused [1,2,4]triazole nucleus was achieved via the reaction of 26 with the appropriate hydrazonyl chlorides 10. [24] Thus, compound 26 reacted with hydrazonyl chloride 10a in dioxane in the presence of an equivalent amount of triethylamine. The reaction mixture was heated at reflux till no methanethiol gases were evolved.…”
Section: Chemistrymentioning
confidence: 99%
“…Pyrimidines and their related fused heterocyclic derivatives possess antibacterial, antifungal, antiviral, anti-influenza, antioxidant, anti-inflammatory, antimalarial, antiproliferative, and antitumor activities. [20][21][22][23][24] Our research group has published many researches in the field of synthesis of pyrimidine derivatives and their related fused heterocyclic derivatives, [25][26][27][28][29][30] because they possess broad spectrum of bioactivities. [17][18][19] Moreover, [1,2,4] triazolopyrimidine derivatives exhibit antimicrobial, antifungal, antioxidant, anti-inflammatory, antimalarial, analgesic, and antitumor activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, literature survey revealed that pyrazoline derivatives possess a broad spectrum of biological activities including anticancer, antiinflammatory, antihypotensive, antidepressant, anticonvulsant, antimicrobial, and antitubercular activities [12][13][14][15][16][17][18]. Moreover, triazolo [4,3-a]pyrimidines has antimicrobial and anticancer [19][20][21] activities. Based on these observations, it was of interest to incorporate benzofuran ring system into different heteroaryl ring systems in one molecule in an attempt to obtain a new target anticancer agents.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 In the last two decades we have been involved in a program aiming at the synthesis of functionally substituted heterocyclic compounds from cheap laboratory available starting materials with anticipated biological activities. [12][13][14][15][16][17][18][19][20] Recently, in the frame of our program, some new functionally substituted thiazoles and / or bisthiazoles were required to be screened for their biological activity as antitumor agents. It seemed to us that the combination of a thiazole ring with a pyridine ring in one entity may lead to enhanced biological activity due to the synergistic effect of both rings.…”
mentioning
confidence: 99%